Educational Video to Improve Glycemic Control of Type 2 Diabetes Mellitus Patients - Nora Wulandari; Daniek Viviandhari; Afi Seli Febriani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Glycemic control is a critical point in the management of type 2 diabetes mellitus (T2DM). The limited number of pharmacists in primary health care in Indonesia is one of the reasons that a simple alternative method is needed for managing T2DM patients. Objective: This study aimed to measure the effectiveness of an education diabetes video as a simple method of improving glycemic control of T2DM patients. Methods: This was a quasi-experimental pre-test/post-test study involving T2DM patients from one randomly selected public healthcare centre in East Jakarta. Glycated haemoglobin (A1C) levels were examined before and 12 weeks after the video intervention. Results: Thirty of T2DM patients enrolled in this study. The educational video was found to decrease the A1C level significantly (p = 0.001) from an average±SD of 7.930±1.262 to 5.517±0.614. Conclusions: This study found the educational was effective at improving the glycemic control of patients with T2DM. However, further investigation with control group still needed to confirm that the video that did it.